Fouling characteristics of membrane filtration applied to wastewater - Thomas, M. H. (Cranfield University, 1998)
The use of microfiltration and ultrafiltration in waste water treatment is attracting increasing interest. The problem of membrane fouling and the high costs associated with the process has limited large scale applications. This study forms part of a project to optimise the design of a membrane bioreactor. A pilot plant has been used to assess the performance of three tubular membrane modules. The wastewater used has been taken from an existing biological reactor to simulate the conditions found in a membrane bioreactor. Commercially available membrane modules of different specification have been tested. The study has centred around the fouling characteristics of the membranes under varying operating conditions. The flux produced after 24 hours continuous operation has been used to assess the degree of fouling present. The hydrodynamic conditions have been varied, and an optimal cross flow velocity range has been identified. The feed wastewater has been varied, and the specific flux at different MLSS concentrations recorded. The specific flux shows a decline with increasing MLSS concentration. The magnitude and rate of this decline is membrane dependant. The permeate product water shows a reduction of more than 99% for SS, BOD, and COD over the feed stream under all conditions used. The DOC also shows a reduction of up to 72%, indicating that the membranes reject a portion of the high molecular weight molecules present in the feed stream. The energy consumption has been estimated from the final permeate flux produced under each set of conditions. The lowest value has been found to be 1.75 kWhm-3, which was achieved at the lowest cross flow velocity used during the trials. This illustrates the influence of pressure drop through the system, which is proportional to the flow velocity squared.